The Use Of Supply Chain Management To Reduce Delays In Public Road Projects In Jordan - Alhawatmeh, Omar Saleh Okleh (2023)
This thesis is investigating the use of supply chain management (SCM) to decrease the phenomena of road project delays. Delays in the completion of highways have been the focus of investigation for decades. Jordan have been significantly impacted by this quandary, especially in public-sector undertakings, particularly road projects. The delay rates were exorbitant. In this study, the study must explore the causes of road project delays in Jordan. Research was done at the implementation site for organisations participating in the execution of road projects. The qualitative data approach is used where data is collected through semi-structured interviews with the individuals concerned for the implementation of road projects. Document reviews, informal conversations, and notes are also used to support statements from interviews. The data was analysed by including data in the analysis program (NVivo 12), where the results of this study are based on the theory of the land. From the results of the study, it appears that laws and government change orders, poor funding and shortages of workers in the sector, reasons related to contractors such as difficulty of financing and inability to provide the project capital. High prices of materials are among the main factors causing delays in project delivery. Appropriate (SCM) approaches from the literature were identified and used (together with tools proposed by industry practitioners) to create a comprehensive framework for reducing delays in Jordanian road projects. Finally, this approach includes important (SCM) tools for the reduction of specific infections and delayed pathogen subclasses.